Teaching English Prose Using Multimedia at Universities (Journal of Educational Sciences, 2025)
The article presents methodological recommendations on the use of feature films in world literature classes. The lack of motivation among students to read fiction worries teachers, and therefore we are talking about the need to make the learning process more effective and interesting. To achieve the learning objective in the lesson, the necessity of using films is proposed, and the experience of using video films in literature lessons is described. Film versions of prose written in English are specially considered at the lessons of foreign literature of the university. When watching a movie in English or Russian, students are offered tasks and elements of the methodology of work. A systematic list of feature films based on works in English that can be used in the educational process of higher education is proposed. The article discusses ways for the university to use effectively the possibilities of film versions in foreign literature lessons. It describes the experience of using films based on the work in teaching English prose. It also shows aspects that require special attention when working with a video. The study examines ways to effectively use the possibilities of film versions based on works of fiction. Using the example of a comparative analysis of an episode of a work of art and a fragment from a movie created based on this work; the system of working with students is shown. The juxtaposition of literary text and cinema gives students scope for independent creative work, for research. In the process of this comparison, aesthetic taste develops; “one’s own point of view” is formed. The circle of literary interests deepens and expands; great opportunities for the development of speech open up. In the empirical part of the study, 42 students of the Kazakh National Women’s Pedagogical University took part. The authors of the article concluded that the screening of works of world literature, in addition to deep immersion in the literary text, contributes to the formation of aesthetic feeling and aesthetic evaluation, develops analytical skills and creative thinking.Key words: higher education, teaching methodology, electronic teaching aids, video film, foreign literature.